Origin of Ovarian Cancer: Molecular Profiling - Dutta, Dilip Kumar; Dutta, Indranil (Journal of obstetrics and gynaecology of India, 2013)
This is a review on the transition from our empirical approach to treat ovarian cancer to a specific treatment based on molecular signature. We have reviewed not only the evidence-based medicine focused on the origin and tumor morphology of ovarian cancer but also the molecular signature era based on molecular phenotyping of the tumor and its microenvironment, which influences the direct targeted therapy. Evidence-based medicine has shown that the targeted therapy studies are mainly biomarker driven, more focused, and hence treat only those patients who have the underlying molecular abnormality. This molecular abnormality is the target of the drug, leading to higher rates of response. These findings will carry important implications for screening, detection, and treatment of ovarian cancer in the future.